Construction of Yersinia pestis Strain Producing Fluorescent Protein GFP and Prospects of Its Usage - L. M. Kukleva; I. V. Tuchkov; E. G. Oglodin; Z. L. Devdariani; O. A. Morozov; O. S. Kuznetsov; V. G. Germanchuk; G. A. Eroshenko (Проблемы особо опасных инфекций, 2020)
Objective of the study was to construct the recombinant Y. pestis strain producing fluorescent protein GFP and analysis of the prospects of its usage for investigation of interaction of the agent with the protozoa, and also macroorganism of mammals (rodents). Materials and methods. To create the strain producing fluorescent protein GFP, we used the natural Y. pestis strain isolated in 2016 in Gorno-Altai high-mountain plague focus. Fluorescent protein gen was inserted into commercial vector pTurboGFP-B via electroporation. Properties of the obtained recombinant Y. pestis strain 367 pTurboGFP-B were studied using microbiological, biological, and molecular-genetic methods. Results and conclusions. The plague agent strain, containing vector plasmid pTurboGFP-B which encodes synthesis of green fluorescent protein GFP, and being resistant to ampicillin was constructed applying electroporation. The designed Y. pestis strain, producing green fluorescent protein, does not differ from the stock strain by its cultural-morphological, biochemical properties, virulence and survivability in mixed culture with Acanthamoeba castellani. On solid nutrient media, recombinant strain and its subcultures, obtained from infected animals, formed colonies of greenish-yellow color, becoming fluorescent under UV-light. In preparations from animals and from co-cultures with amoeba, fluorescent cells of plague agent were observed. The constructed strain can be utilized as a model one for investigation of interactions between plague agent and cells of protozoa (soil amoeba, nematodes) and mammals under laboratory conditions.